Syntactic Priming As a Test of Argument Structure: A Self-paced Reading Experiment - Oltra-Massuet, Isabel; Sharpe, Victoria; Neophytou, Kyriaki; Marantz, Alec (Frontiers in Psychology, 2017)
Using data from a behavioral structural priming experiment, we test two competing theoretical approaches to argument structure, which attribute different configurations to (in)transitive structures. These approaches make different claims about the relationship between unergatives and transitive structures selecting either a DP complement or a small clause complement in structurally unambiguous sentences, thus making different predictions about priming relations between them. Using statistical tools that combine a factorial 6 x 6 within subjects ANOVA, a mixed effects ANCOVA and a linear mixed effects regression model, we report syntactic priming effects in comprehension, which suggest a stronger predictive contribution of a model that supports an interpretive semantics view of syntax, whereby syntactic structures do not necessarily reflect argument/event structure in semantically unambiguous configurations. They also contribute novel experimental evidence that correlate representational complexity with language processing in the mind and brain. Our study further upholds the validity of combining quantitative methods and theoretical approaches to linguistics for advancing our knowledge of syntactic phenomena.